2016
DOI: 10.1101/065391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distal axotomy enhances retrograde presynaptic excitability onto injured pyramidal neurons via trans-synaptic signaling

Abstract: Injury of CNS nerve tracts remodels circuitry through dendritic spine loss and hyper-excitability, thus influencing recovery. Due to the complexity of the CNS, a mechanistic understanding of injury-induced synaptic remodeling remains unclear. Using microfluidic chambers to separate and injure distal axons, we show that axotomy causes retrograde dendritic spine loss at directly injured pyramidal neurons followed by retrograde presynaptic hyper-excitability. These remodeling events require activity at the site o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 67 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Primarily axons of pyramidal neurons are guided via microgrooves into a separated axon compartment where they are injured and various pharmacological treatments can be restricted to isolated axons. We previously found that blocking local activity at the site of injury using this method prevented dendritic spine loss 24 h post-axotomy (Nagendran et al 2017), suggesting calcium and sodium influx at the site of injury are key mediators of this neuronal injury response. Reversal of NCX at the site of injury may play a key role, causing this massive local influx of calcium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primarily axons of pyramidal neurons are guided via microgrooves into a separated axon compartment where they are injured and various pharmacological treatments can be restricted to isolated axons. We previously found that blocking local activity at the site of injury using this method prevented dendritic spine loss 24 h post-axotomy (Nagendran et al 2017), suggesting calcium and sodium influx at the site of injury are key mediators of this neuronal injury response. Reversal of NCX at the site of injury may play a key role, causing this massive local influx of calcium.…”
Section: Resultsmentioning
confidence: 99%
“…Axon injury induces differential gene expression and transcription within the soma, requiring long range signaling from the site of injury to the nucleus (Rishal and Fainzilber 2014; Nagendran et al 2017). Breach of the axonal membrane following axon injury causes an influx of ions, including calcium and sodium, into the intra-axonal space.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microfluidic cultures were immunostained to detect phospho-cJun (pcJun) and Neurofilament. The retrograde signaling is tracked from uninjured and injured axon chambers on either side to the central cell body chamber (Holland et al, 2016) range axotomy (Nagendran et al, 2017). Using microgrooves 900 μm in length, Nakatomi et al (2002) examined the effect of axotomy on synaptic remodeling similar to in vivo conditions where long projection neurons are affected far from the site of CNS injury.…”
Section: Et Al (2012)mentioning
confidence: 99%